Monitoring training and fatigue with heart rate variability: Case study in a swimming Olympic champion - Schmitt, L.; Regnard, J.; Auguin, D.; Millet, G. P. (Journal of Fitness Research, 2016)
Introduction: Training loads and heart rate variability (HRV) were monitored over 69 weeks in a swimming Olympic champion to assess if different types of HRV changes occurred during fatigue episodes.